Konseling Islam untuk Meningkatkan Kematangan Emosi bagi Pasangan Pernikahan Usia Dini - Achmad Syaefudin (Universitas Muhammadiyah Magelang, 2020)
Early marriage involves a person that is below 18 years old, the age people are considered to be emotionally mature to live in a household. This study aims to describe possible household problems and determine the effect of Islamic counseling on the emotional maturity of early married couples. A mix-method with experimental research was used and the subjects are 16 early married couples who got married in 2016 in the KUA of Pakis District, Magelang. The results showed that the problems that occur in early marriages are due to the economy, conflict with parents, adaptation to the environment, and household violence. Also, the results of the Wilcoxon analysis showed that there was a significant difference in the level of emotional maturity of early married couples after Islamic Counseling.